The Development Of Grading Practices Inventory And The Differences Of Grading Practices Among Academic And Religious Teachers In Thailand - Duerama, Mayuti (2018)
Assessment and grading is a professional responsibility for teachers to carry out teaching and make conclusions about students’ learning outcome. The process of assessment and grading can be varied among teachers in different situations and contexts. Thus, to understand the practice of assessment and grading among teachers is essential for improving teacher’s capability in assessment and grading. The primary purpose of this study was to develop and evaluate psychometric properties of the Grading Practice Inventory (GPI), and to examine the invariance profiles of teachers’ grading practices across different disciplines. In this study, 1394 teachers teaching religious subjects and academic subjects in Islamic private schools in southern Thailand were involved, and the Rasch Rating Scale Model (RRSM) and Confirmatory Factor Analysis (CFA) were applied to analyse the data. The results revealed that the GPI is a valid and reliable instrument to measure teachers’ grading practices. The analysis of psychometric properties indicated that content validity was adequate, the construct validity was satisfactory, and the reliability was high. The results of Rasch analysis suggest that the GPI was unidimensional, and all items functioned similarly across two group of sample teachers. The results of multi group CFA analysis showed that the GPI model is an acceptable fit to the data across two groups lending to support that the model was invariant. The results of the analysis indicate that teachers in academic and Islamic subjects differed in using assessment methods, considering grading factors, and determining the grading process. This study provided a beneficial understanding of teachers’ grading practices across academic and Islamic subject areas.